Iron oxide nanoparticles decorated oleic acid for high colloidal stability - Lai, Chin Wei; Low, Foo Wah; Tai, Mun Foong; Hamid, Sharifah Bee Abd (Wiley, 2017)
In the present study, oleic acid (OA)-decorated magnetite nanoparticles (MNPs) were synthesized via in situ co-precipitation method using ammonium hydroxide as a precipitating agent. This study aims to determine the optimum loading amount of OA for improving the MNPs colloidal stability. Based on our results obtained, it was found that the zeta potential values of MNPs increased from −29.8 to −58.1 mV after modification of MNPs with 1.2 wt.% of OA. Indeed, results obtained clearly to show that a maximum colloidal stability of MNPs in a basic medium could be significantly improved. As a result, this resultant colloidal suspension performance was approximately 7 times higher (21 days- high colloidal stability against precipitation and agglomeration) than that of the undecorated MNPs sample (3 days). Based on vibrating sample magnetometer (VSM) analysis, the resultant OA-decorated MNPs exhibited superparamagnetic behavior with slightly lower saturation magnetization (51–69 emu/g) than that of undecorated MNPs sample (80 emu/g) at room temperature. This behavior was attributed to the sufficient carboxylate ions from the outer layer of the bilayer of OA-decorated MNPs, which promoted the high colloidal stability performance.